Accounting principles - Weygandt, Jerry J.; Kimmel, Paul D.; Kieso, Donald E. (John Wiley & Sons, 2019)
Accounting Principles, global edition continues to provide students with a trusted and clear introduction to fundamental accounting concepts, which has made this best-selling text so popular. Helping students get the most out of their accounting course by making practice simple, the new edition continues to present the accounting cycle from a sole proprietor perspective, whilst providing the latest IFRS integration throughout (separate references to GAAP are made at the end of each chapter for courses where needed). To maximise student achievement a plethora of additional teaching and learning resources will be available including self-tests, exercises, templates, videos and more. Using metric units and companies with a more global feel, this new text is ideal for courses across the world.